Destinasi Wisata Alam Gunung Mayana sebagai Kontributor Pengembangan Perekonomian Masyarakat Desa Sindangjawa - Nurhaliza, Ai Siti; Suryaman, Oman; Hidayat, Achmad Nur; Susnandi, Andi (Universitas Nusantara PGRI Kediri, 2024)
Indonesia has great potential as an attractive tourism destination, with its natural beauty, diverse cultures, and the friendliness of its people. Kuningan Regency, especially Mount Mayana, has significant natural attractions that have the potential to boost the local economy, but there are still challenges in terms of accessibility. This research aims to describe the local potential of Mount Mayana as a natural tourism destination and how it can contribute to the economic development of Sindangjawa Village. The research method used in this study is descriptive qualitative, where data is collected through observation, interviews, and documentation. The findings of this research indicate that Mount Mayana has significant potential as an attractive natural tourism destination. This potential includes beautiful natural scenery, sacred tombs that can be a religious tourist attraction, a road network connecting four villages, areas for implementing business development plans such as fruit agrotourism, grass track areas, eco-friendly villas, camping areas, Javanese eagles, and the Mount Mayana Forest Area with high potential for medicinal plants. To optimize this potential, there needs to be collaboration between the government, military institutions, and the local community. Development steps, such as improving accessibility, empowering the local community, and effective promotion, can contribute to the long-term economic growth and the preservation of the natural and cultural heritage of Mount Mayana.